Key Informants Specify Core Elements of Peer Supports for Parents With Serious Mental Illness - Nicholson, Joanne; Valentine, Anne (Frontiers in Psychiatry, 2019)
Background Researchers have documented the lack of evidence-based interventions for parents with serious mental illness (SMI). Given the prevalence of parenthood among individuals with SMI, the value placed on parenthood, and their diverse vulnerabilities, a robust, theoretically sound and empirically tested model of peer supports would likely provide a valuable complement to psychiatric services. In this paper, we lay the groundwork for a model of peer supports using a program theory development process and guided by stages of evidence-informed innovation outlined by the National Implementation Research Network. Methods This study employed a developmental design in the initial stage of a larger study of the development, implementation and testing of peer supports to address three questions: (1) What needs of parents with SMI are particularly well-suited to peer supports? (2) What do peers have to offer parents? and (3) What is unique about peer supports for parents? A purposeful sampling strategy was used to recruit key informants (n = 22) familiar with peer supports, family-focused care and the experiences of families living with parental mental illness. Individual interviews were conducted face-to-face or on the telephone and a full-day group interview was conducted using a workshop format. Interview data were analyzed qualitatively to identify themes reflecting potential core program elements. Results Consistent themes drawn from data comprise four core program elements: engage, explore, plan, and access and advocate. These core activities are likely founded on practice principles that include a focus on families and their strengths, cultural sensitivity, and acknowledgement of the trauma experienced by many parents. The findings raised a number of challenges in contemplating peer supports for parents with SMI, including the need for ongoing support for peers. Discussion In developing this model, aspects of organizational context must be considered along with specification of the characteristics of parents with SMI suited to this approach and the attributes of peers providing support. A fully-articulated model must include parallel theories of change for the workforce, as well as for participating parents, to support wellbeing in the context of peer relationships and the success of parents with SMI in family life.